On the Structural Uniformity of Superlatives: Evidence from Georgian, Slovene, and Tamil - Subhalaxmi Chidambaram, Vrinda (Slovenski jezik / Slovene Linguistic Studies, 2024)
This paper is an exploration of the structure of superlative degree adjectives and the syntactic constructions in which they occur across three very distinct languages. Slovenian, Georgian, and Tamil each represents a typological variant of the superlative construction. Slovenian has synthetic superlatives, built from the naj- prefix, while Georgian and Tamil have compositional superlatives, in which the meaning of the superlative is derived compositionally. In this paper, I show that these apparent differences between these constructions is superficial and that the underlying syntax is largely the same.